San Antonino's Bold Welfare Initiative (Hispanic Business: Women in Business)
Welfare is a drag. No place to be. It's poverty. Two, three-year old kids running around a project apartment, without bottoms or tops, crying and carrying on desperately. Everything is unkempt: The kitchen, bedrooms, bottles of pop and fast food goodies are scattered about, the TV's picture is rolling aimlessly, and the woman head of this household of four (3 children, one woman adult) is madder than a hatter because she's got nothing to do.